Prevalence of methicillin-resistant Staphylococcus aureus and other pathogens in pus samples of orthopedic department at a tertiary care hospital in Pakistan (Medical Journal of Indonesia, 2019)
BACKGROUND Orthopedic infections are difficult to manage. Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most dangerous and harmful bacteria and is difficult to eradicate because of its changing strains as well as sensitivity to different antibiotics. The main aim of this study was to determine the prevalence of pathogens, especially MRSA, associated with orthopedic wounds and their sensitivity to different antibiotics. METHODS A prospective study was conducted from September 2015 to August 2016. Pus samples of 1,350 patients who presented at the out-patient department or admitted with a wound infection after an orthopedic intervention were taken with the help of culture swab and were sent for culture and sensitivity according to hospital protocol. Data analyses were made using the SPSS software, version 17 (IBM). RESULTS Adults aged between 15 and 30 years were most affected, with 444 (32.9%) cases. Of the patients, 268 (19.9%) had negative cultures. Among the patients with positive cultures, the gram-positive cocci and gram-negative rods were 497 (36.8%) and 377 (27.9%), respectively. The most common pathogen was MRSA (240; 17.8%), followed by Escherichia coli and methicillin-sensitive S. aureus. CONCLUSIONS Multiple pathogens are involved in patients having an orthopedic surgical intervention. The high occurrence of MRSA and E. coli has an increasing economic burden on patients because of these pathogens high resistance to antibiotics. Thus, proper preventive measures should be done to decrease the occurrence of such infections as well as their associated morbidity.